PENDEKATAN MODEL KOMPUTASI UNTUK PENANGGULANGAN SEDIMENTASI PELABUHAN AKIBAT PENGARUH MUARA SUNGAI: STUDI KASUS PELABUHAN TANJUNG MAS SEMARANG - Huda Bachtiar, S. Si., M. SC (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
Shoaling due to sedimentation process leads to the problem of port operation, where ships have a problem to navigate inside the port. The problem of the operation can lead to the reduction of the profit margin for the port. This paper discusses the engineering solution to solve the sedimentation problem because of the estuary inflow. In order to analyze the sedimentation behavior, computational model deploys as a tool for the assessments. The simulation results are validated by observation data; water level observation one month and current measurement for fifteen days. Simulation results show that the sedimentation in Tanjung Mas port mostly because of estuary inflow in the West and in the East side of the port with maximum suspended sediment concentration around 0,15 kg/m3. Sedimentation problems can be solved both by dredging and refunctioning of the breakwater. In the dredging process, the existing dumping area has an appropriate location since the sedimentation dispersion still in the offshore area. Refunctioning of the breakwater can also reduce the sedimentation effectively, it is shown by morphological model results where siltation process both near the navigation channel and inside the port can be blocked by the structure.